1999
DOI: 10.1007/s002130050804
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and naloxone combinations: the effects of three dose ratios in morphine-stabilized, opiate-dependent volunteers

Abstract: Sublingual buprenorphine is a promising new treatment for opiate dependence, but its opioid agonist effects pose a risk for parenteral abuse. A formulation combining buprenorphine with the opiate antagonist naloxone could discourage such abuse. The effects of three intravenous (IV) buprenorphine and naloxone combinations on agonist effects and withdrawal signs and symptoms were examined in 12 opiate-dependent subjects. Following stabilization on a daily dose of 60 mg morphine intramuscularly, subjects were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Although the present study showed no differences in the reinforcing effects of buprenorphine compared with the buprenorphine/naloxone combination in nondependent individuals, it is likely that different results would have been obtained in opioid-dependent individuals. The buprenorphine/naloxone combination has mostly antagonist-like effects in individuals maintained on morphine (Fudala et al, 1998;Mendelson et al, 1999), hydromorphone (Preston et al, 1988;Stoller et al, 2001), or methadone (Bigelow et al, 1987;Mendelson et al, 1997). What is not clear, however, is whether buprenorphine or the combination has abuse liability in individuals maintained on buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study showed no differences in the reinforcing effects of buprenorphine compared with the buprenorphine/naloxone combination in nondependent individuals, it is likely that different results would have been obtained in opioid-dependent individuals. The buprenorphine/naloxone combination has mostly antagonist-like effects in individuals maintained on morphine (Fudala et al, 1998;Mendelson et al, 1999), hydromorphone (Preston et al, 1988;Stoller et al, 2001), or methadone (Bigelow et al, 1987;Mendelson et al, 1997). What is not clear, however, is whether buprenorphine or the combination has abuse liability in individuals maintained on buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…The opioid receptor ligands significantly influence the respiratory system (Bartho et al, 1987;Belvisi et al, 1990Belvisi et al, , 1992. In general, the opioid agonists produce respiratory depression (Haji et al, 2000), as it was observed for morphine (Kato, 1998;Takita et al, 1998;Weinger et al, 1998;Gwirtz et al, 1999;Mendelson et al, 1999;Osterlund et al, 1999;Sleigh, 1999;Czapla et al, 2000;Dershwitz et al, 2000;Heishman et al, 2000;Herschel et al, 2000;Hill and Zacny, 2000;Kishioka et al, 2000a,b;Krenn et al, 2000;Owen et al, 2000;Takita et al, 2000;Teppema et al, 2000), heroin (Vivian et al, 1998; Comer et al, 1999; Kishioka et al, 2000b), fentanyl (Gerak et al, 1998;Kishioka et al, 2000b), buprenorphine (Benedetti et al, 1999;Schuh et al, 1999), and DAMGO (Takita et al, 1998;Czapla et al, 2000), although some exceptions were reported (Greenwald et al, 1999;Mendelson et al, 1999;Angst et al, 2000;Czapla et al, 2000;Preston and Bigelow, 2000). Whereas numerous mechanisms are involved in respiratory regulation, the primary mechanism thought to be involved in opioid-induced respiratory depression is a general decrease in the sensitivity of brainstem respiratory centers to carbon dioxide, followed by a decrease in respiratory rate (for review, see Martin, 1983;…”
Section: A Biological Effects Of Endomorphinsmentioning
confidence: 96%
“…The low bioavailability of naloxone through the sublingual route allows appropriate intake, while opiate agonist effects are attenuated in the case of parenteral administration. Injection even precipitates withdrawal symptoms in opiate-dependent subjects [32][33][34] , which reduces the abuse potential of the combination tablet. However, it is less clear how the addition of naloxone affects the abuse potential in opiate-naïve or nondependent individuals.…”
Section: Discussionmentioning
confidence: 99%